Benefits of Exercise Training for Children and Adolescents Undergoing Cancer Treatment: Results From the Randomized Controlled MUCKI Trial - Stössel, Sandra; Neu, Marie A.; Wingerter, Arthur; Bloch, Wilhelm; Zimmer, Philipp; Paret, Claudia; Malki, Khalifa El; Baumann, Freerk T.; Russo, Alexandra; Henninger, Nicole; Lehmann, Nadine; Otto, Henrike; et al. (Frontiers in Pediatrics, 2020)
Objective: In cancer patients, the impairment in muscle function is a frequently observed phenomenon. However, comprehensive evaluation of the effect of exercise training on muscle function in childhood cancer patients (CCP) is sparse and therefore investigated in the MUCKI trial. Study design: In the randomized controlled MUCKI trial, CCPs during intensive cancer treatment and aged 4 to 18 years were recruited. Eligible patients were enrolled as soon after diagnosis as they were physically and mentally able to participate in exercise testing and training. Patients of the exercise group (n = 16) participated in average 2.7 ± 1.2 times per week in a combined resistance and endurance training with moderate exercise intensity, for a time period of 8.0 ± 2.1 weeks, while patients of the control group (n = 17) received usual care. Leg strength was evaluated as the primary endpoint. Secondary endpoints were six-minute walk performance, arm strength, body composition, fatigue and health-related quality of life. Results: Comparison of pre- and post-intervention results were evaluated by baseline and stratification criteria adjusted analysis and showed positive effects for the exercise group regarding to leg strength (F(1,20) = 5.733; p = 0.027*; η2p = 0.223), walking performance (F(1,25) = 4.270; p = 0.049*; η2p = 0.146), fatigue (F(1,13) = 8.353; p = 0.013*; η2p = 0.391), self-esteem (F(1,6) = 6.823; p = 0.040*; η2p = 0.532) and self-reported strength and endurance capacity (F(1,6) = 6.273; p = 0.046*; η2p = 0.511). No significant differences were found for the other parameters. Conclusion: Within one of the first randomized controlled trials, the present study provides evidence for a positive effect of combined training in CCP during intensive cancer treatment. Further research is needed to confirm these results and to evaluate their clinical impact.